2009
DOI: 10.1080/10715760903071664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-citrulline oral supplementation on polymorphonuclear neutrophils oxidative burst and nitric oxide production after exercise

Abstract: Seventeen volunteer male professional cyclists were randomly assigned to control or supplemented (6 g L-citrulline-malate) groups and participated in a cycling stage. Blood samples were taken in basal conditions, after the race and 3 h post-race. Citrulline supplementation significantly increased plasma concentration of both arginine and citrulline after the stage only in the supplemented group. Polymorphonuclear neutrophils (PMNs) from controls responded to exercise with a progressive decrease in ROS producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 52 publications
1
77
0
Order By: Relevance
“…Much evidence suggests that L-citrulline can decrease suppress oxidative damage induced by exhaustive exercise. 15 Moreover, L-citrulline can become the effective precursor of L-arginine which is a substrate for endothelial NO synthase (eNOS) via the L-citrulline/L-arginine pathway, and plays an important role in the metabolism and regulation of NO. 16 Others demonstrated that oral supplementation of L-citrulline can inhibition the increased inducible nitric oxide synthase (iNOS) activity, upregulate endothelial NO synthase (eNOS) activity, and improve endothelial function in animal.…”
Section: Introductionmentioning
confidence: 99%
“…Much evidence suggests that L-citrulline can decrease suppress oxidative damage induced by exhaustive exercise. 15 Moreover, L-citrulline can become the effective precursor of L-arginine which is a substrate for endothelial NO synthase (eNOS) via the L-citrulline/L-arginine pathway, and plays an important role in the metabolism and regulation of NO. 16 Others demonstrated that oral supplementation of L-citrulline can inhibition the increased inducible nitric oxide synthase (iNOS) activity, upregulate endothelial NO synthase (eNOS) activity, and improve endothelial function in animal.…”
Section: Introductionmentioning
confidence: 99%
“…Cell lysates were stored at −80 °C until biochemical analyses. Venous blood samples were obtained after 12 h, overnight, fasted conditions (basal sample), and 2 h after finishing training as this is coincident with an increment in circulating immune cells, with changes in antioxidant enzymes activities and in markers of oxidative damage [29,30].…”
Section: Methodsmentioning
confidence: 99%
“…This cycle is physiologically significant because it constantly recycles Cit in order to maintain a sufficient concentration of Arg within cells [66]. For example, male cyclists who received 6 g Cit supplementation prior to cycling events showed increased plasma levels of Cit, Arg and NO concentrations [67]. Cit is therefore of paramount importance in the body.…”
Section: Arginine Synthesismentioning
confidence: 99%